Electrocatalysts: A Facile Strategy to Construct Amorphous Spinel‐Based Electrocatalysts with Massive Oxygen Vacancies Using Ionic Liquid Dopant (Adv. Energy Mater. 27/2018). Issue 27 (25th September 2018) - Sun, Jing; Guo, Niankun; Shao, Zhiyu; Huang, Keke; Li, Yaowen; He, Feng; Wang, Qin
Abstract : Article number1800980 by Feng He, Qin Wang and co‐workers showcases a study of an amorphous spinel‐based catalyst with massive oxygen vacancies using an ionic liquid‐dopant. This work introduces oxygen vacancies into an amorphous heteroatom doped CoFe2 O4 catalyst using an ionic liquid‐dopant, and simultaneously anchors ultrafine MoS2 nanoclusters onto its surface to increase the specific surface area and oxygen evolution reaction catalytic performance.